Evolving co-adapted subcomponents in assembler encoding - Praczyk, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a new Artificial Neural Network (ANN) encoding method called Assembler Encoding (AE). It assumes that the ANN is encoded in the form of a program (Assembler Encoding Program, AEP) of a linear organization and of a structure similar to the structure of a simple assembler program. The task of the AEP is to create a Connectivity Matrix (CM) which can be transformed into the ANN of any architecture.
Keywords: neural networks; evolution; neuroevolution